Transfusion [videorecording (DVD)] - Nable, Matt; Nable, Matt; Worthington, Sam, 1976-; Tonkin, Phoebe, 1989- (Saban Films, 2023)
Ex-special forces operative Ryan Logan has a sharply honed set of survival skills that have allowed him to walk the line between courage and fear. But after a personal tragedy shatters his family and sends his teenage son, Billy, into a world of drugs and delinquency, he is pushed to the edge. Desperate to make a new life for Billy, Ryan plunges into the criminal underground for one final mission in this muscular, emotionally charged thriller.